PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CV. THINK DESIGN PRINT GADING SERPONG TANGERANG - Rohmah, Fitriya; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of work motivation and work discipline on the performance of CV. Think Design Print in Gading Serpong Tangerang both partially and simultaneously. The method used is the Descriptive Quantitative method. The population in this study is CV. Think Design Print ini Gading Serpong Tangerang. The sampling technique used was the saturated sample method with a sample of 60 respondents. The data analysis method used vality test and reliability test, data normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and F test. The results of this study show that there is a positive and significant influence of work motivation on employee performance on CV. Think Design Print in Gading Serpong Tangerang: This can be proven from the simple linear regression equation Y = 10.961 + 0.764X. The correlation value is 0.698 (strong). The value of the determination coefficient is 48.8% (strong), the value of tis 7,432 > 1,672 with a significance of 0.000 < 0.05. There is a positive influence and significance of work discipline on the performance of CV. Think Design Print in Gading Serpong Tangerang This can be proven from the simple linear regression equation Y = 7.479 + 0.723X. Correlation value 0.722 (strong). The value of the determination coefficient is 52.2% (strong), the t-value is 7,955 > 1,672 with a significance of 0.000 < 0.05. Simultaneously there is a positive and significant influence of work motivation and work discipline on CV. Think Design Print in Gading Serpong Tangerang  is proven by the multiple linear regression equation Y = 6.273 + 0.385X1 + 0.454X2. The correlation value is 0.757 (strong), the determination coefficient value is 57.3%, the F value is calculated 38,262 > 3.159 with a significant level of 0.000 < 0.05.